Do low vitamin D levels facilitate renal parenchymal injury? - Mervan Bekdas; Billur CalÄ±skan; Seyda Karabork; Seher Acar; Nimet Kabakus (Indonesian Pediatric Society, 2020)
Background Decreased vitamin D levels lead to an increase in infectious diseases, including urinary tract infections (UTIs). Objective To assess serum vitamin D levels in children with renal parenchymal injury secondary to UTIs. Methods Forty-three upper UTI patients and 24 controls, aged 1–15 years, were included. Vitamin D levels and other laboratory tests were obtained when they first admitted to hospital. 99mTc-labeled dimercaptosuccinic acid (DMSA) scans were performed to evaluate renal parenchymal injury. Results Mean serum 25-hydroxyvitamin D (25(OH)D) was lower in the upper UTI group compared to the control group [18 (SD 9) vs. 23 (SD 10.6) ng/mL, respectively; P=0.045]. The upper UTI group was sub-divided into two groups, those with 22 (51.1%) and without 21 (48.8%) renal parenchymal injury. Mean 25(OH)D was significantly lower in patients with renal parenchymal injury [15.1 (SD 7.1) vs. 21 (SD 9.9) ng/mL, respectively; P=0.03]. The renal parenchymal injury cases were further sub-divided into two groups: 8 patients (36.3%) with acute renal parenchymal injury and 14 (63.6%) with renal scarring (RS), but there was no significant difference in 25(OH)D between these two groups [12.5 (SD 8.9) vs. 16.6 (SD 5.7) ng/mL, respectively; P=0.14). Conclusion Decreased vitamin D is associated with renal parenchymal injury in children with upper UTIs. However, vitamin D is not significantly decreased in renal scarring patients compared to acute renal parenchymal injury patients.